2013
DOI: 10.1161/hypertensionaha.113.01701
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interaction Between Sympathetic Overactivity and Aberrant Regulation of Renin by miR-181a in BPH/2J Genetically Hypertensive Mice

Abstract: BPH/2J mice are a genetic model of hypertension developed by Schlager 1 by crossing 8 normotensive strains and selecting for elevated blood pressure (BP). Normotensive BPN/3J control mice were bred concurrently by crossing randomly selected mice from the same base population. Recently, the mechanism of the hypertension has been recognized as neurogenic because ganglion blockade abolished the hypertension in BPH/2J mice.2 Furthermore, spectral analysis of BP revealed greater power in the autonomic frequency ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 22 publications
6
69
0
Order By: Relevance
“…Whole tissue analysis of human nephrectomy specimens has shown that the tubular expression of miR-181a-5p is associated with renin mRNA expression3940. This is in accordance with the finding of an aberrant renal miR-181a-5p expression in mouse41 and human40 hypertensive kidneys. In our small cohort without any differences in arterial blood pressure miR-181a-5p was stably expressed in lasermicrodissected glomeruli with IgA nephropathy, indicating that miR-181a-5p is not primarily affected by IgA-GN or neighboring crescents.…”
Section: Discussionsupporting
confidence: 86%
“…Whole tissue analysis of human nephrectomy specimens has shown that the tubular expression of miR-181a-5p is associated with renin mRNA expression3940. This is in accordance with the finding of an aberrant renal miR-181a-5p expression in mouse41 and human40 hypertensive kidneys. In our small cohort without any differences in arterial blood pressure miR-181a-5p was stably expressed in lasermicrodissected glomeruli with IgA nephropathy, indicating that miR-181a-5p is not primarily affected by IgA-GN or neighboring crescents.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, low-dose AngII-induced hypertension in rabbits, which is accompanied by elevated RSNA, is shown to be associated with greater long-term neuronal activation of the PVN but not the RVLM [60]. This AngII-induced hypertensive model may be particularly similar to the BPH/2J mice since our recent findings also suggest that the hypertension in BPH/2J mice is caused by a greater contribution of the systemic renin-angiotensin system caused by renal hyper-innervation and greater sympathetically induced renin synthesis [61]. Indeed, our own previous findings indicate greater neuronal activity in the PVN but not the RVLM of BPH/2J compared with BPN/3J mice during periods of arousal [1].…”
Section: Discussionmentioning
confidence: 64%
“…Both reduced renal expression of miR-181a and an increase in renin mRNA abundance were associated with hypertension in a small collection of human kidneys (9). miR-181a exhibited an inverse correlation with renin in a genetically hypertensive strain of mice (10). Taken together, these data strongly suggest that this miRNA may constitute a new posttranscriptional layer of control for the ratelimiting enzyme of the renin-angiotensin system (RAS) and, as such, may contribute to BP regulation, thus making it an attractive target for the development of new antihypertensive therapies.…”
Section: Discussionmentioning
confidence: 93%